2022
DOI: 10.1093/jopart/muac038
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing and Explaining Flexibility in Administrative Crisis Management: A Cross-district Analysis in Germany

Abstract: Flexibility in administrative crisis management is a frequently reported determinant for a successful crisis response. But there is little agreement about how to conceptualize, measure and explain flexibility. We use a three-dimensional measure of administrative flexibility, capturing employees’ decision leeway, staff mobility, and organizational innovation in a crisis response. We then develop and test an explanation of variation in flexibility, focusing on the refugee crisis of 2015/16 in Germany and analyzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…One reason is that neoclassical approaches remain central in policy education. For instance, we reviewed curricula of all 17 public management programs for federal and state civil servants and the top 10 law schools in Germany—two of the most popular degrees held by German mayors 30 , 31 —and found that none of these curricula included the above ‘behavioral’ literature on the potential limitations of financial incentives. Another reason is that policy makers make frequent and ongoing use of financial incentives to promote contributions to public goods.…”
Section: Introductionmentioning
confidence: 99%
“…One reason is that neoclassical approaches remain central in policy education. For instance, we reviewed curricula of all 17 public management programs for federal and state civil servants and the top 10 law schools in Germany—two of the most popular degrees held by German mayors 30 , 31 —and found that none of these curricula included the above ‘behavioral’ literature on the potential limitations of financial incentives. Another reason is that policy makers make frequent and ongoing use of financial incentives to promote contributions to public goods.…”
Section: Introductionmentioning
confidence: 99%